Expanded genetic code and Effect of synonymous mutations on expression of Fab fragments - Niemelä, Pyry (My University, 2019)
Antigen binding fragment (Fab) is the part of an antibody which contains an antigen binding site. Fab has many advantages over a conventional antibody such as the reduced size, lack of glycosylation and therefore, the possibility of producing it in bacteria instead of complicated and expensive mammalian cultures. Unfortunately, the yields of Fabs are relatively low in bacterial cultures. Expression of human proteins in bacteria is hindered by different preferences of synonymous codon usage between the two different organisms. This phenomenon is present in all branches of life and is known as codon bias. We created a synonymous mutations library in a CDRH3 region of a lysozyme binding Fab and fused the Fab to an ampicillin cleaving βlactamase. The β-lactamase allows a selection of better expressing variants against an increasing concentration of ampicillin. An increase in the frequency of hits was observed in correlation with increasing ampicillin. At higher concentrations a decreasing trend of Fab expression was observed. At a concentration of 800 µg/ml, the chance of finding a hit more than doubled in comparison to a library without ampicillin selection. The β-lactamase selection of improved Fab expression is a novel method for the selection of synonymous mutation libraries. With optimization of the selection conditions, the results with this basic principle could be improved further. This work consists two parts: a literary review of expanded genetic code and the experimental part concerning β-lactamase selection of Fab fragments from a synonymous mutation library.
Keywords: Fab fragments, synonymous mutation, codon bias, expanded genetic code, genomically recoded organisms